EPIDEMIOLOGICAL PROFILE OF OCCUPATIONAL ACCIDENTS WITH EXPOSURE TO BIOLOGICAL MATERIAL IN THE VALE DO SÃO PATRÍCIO, GOIÁS - 2019 TO 2023 (CIPEEX, 2025)
Occupational accidents involving exposure to biological material represent a significant public health problem, placing workers at risk of contracting infectious diseases through contact with contaminated body fluids. Regulatory Standard 15 (NR-15) and Regulatory Standard 32 (NR-32) were implemented to minimize these risks, establishing guidelines for occupational safety. This descriptive and quantitative study analyzed secondary data from the Notifiable Diseases Information System (SINAN), covering notifications of occupational accidents in two health regions of Ceres, Goiás, which encompass 28 municipalities and a population of 352,318 inhabitants. Preliminary results indicate that accidents involving biological material occur with significant frequency, especially among healthcare professionals. Reporting these incidents to SINAN is essential for monitoring and controlling risks, allowing for the implementation of prevention policies and adequate follow-up of affected workers. Furthermore, the analysis of epidemiological data is crucial for identifying risk groups and improving working conditions, reducing the incidence of accidents. Awareness about the importance of the correct use of Personal Protective Equipment (PPE) and the adoption of safety protocols are essential measures for preventing these injuries.
Keywords: Occupational accidents; Exposure to biological material; Compulsory notification